Öko-logische baukompetenz - Preisig, H. R.; Dubach, U.; Viridén, K.; Dubach, W.; Viridén, K. (Zürich : Wer, 1999)
Handbuch für die kostenbewusste Bauherrschaftvon Abis Z
Keywords: VIVIENDA; CONSTRUCCION; ARQUITECTURA AMBIENTAL; COORDINACION MODULAR; TIPOLOGIAS